Presence of Cryptosporidium spp. and Giardia duodenalis in drinking water samples in the north of Portugal - Almeida, André (2010)
Cryptosporidium and Giardia are 2 protozoan parasites responsible for waterborne diseases outbreaks worldwide. In order to assess the prevalence of these protozoans in drinking water samples in the northern part of Portugal and the risk of human infection, we have established a long term program aiming at pinpointing the sources of surface water, drinking water, and environmental contamination, working with the water-supply industry. Total 43 sources of drinking water samples were selected, and a total of 167 samples were analyzed using the Method 1623. Sensitivity assays regarding the genetic characterization by PCR and sequencing of the genes, 18S SSU rRNA, for Cryptosporidium spp. and b‚-giardin for G. duodenalis were set in the laboratory. According to the defined criteria, molecular analysis was performed over 4 samples. Environmental stages of the protozoa were detected in 25.7% (43 out of 167) of the water samples, 8.4% (14 out of 167) with cysts of Giardia, 10.2% (17 out of 167) with oocysts of Cryptosporidium and 7.2% (12 out of 167) for both species. The mean concentrations were 0.1-12.7 oocysts of Cryptosporidium spp. per 10 L and 0.1-108.3 cysts of Giardia duodenalis per 10 L. Our results suggest that the efficiency in drinking water plants must be ameliorated in their efficiency in reducing the levels of contamination. We suggest the implementation of systematic monitoring programs for both protozoa. To authors’ knowledge, this is the first report evaluating the concentration of environmental stages of Cryptosporidium and Giardia in drinking water samples in the northern part of Portugal.